Susbstance P Levels in Children with Atopic Dermatitis - Khairina Nasution; Deryne Anggia Paramita; Nova Zairina Lubis (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2021)
Background: Atopic dermatitis (AD) is the most common skin disease in infants and children. AD is influenced by hereditary and environmental factors, and it is characterized by an inflammatory reaction in the skin. In developing countries, children suffering from AD are estimated around 10–20%, of which 60% of the cases persist into adulthood. Substance P is a cutaneous neuropeptide that contributes to the pathogenesis of AD. Substance P promotes the production of nerve growth factors from keratinocytes, and the release of histamine, leukotriene, or tumor necrosis factor from mast cells, which cause the growth of sensory nerve fibers, augmentation of skin inflammation, and are considered pruritogenic factors. Purpose: This study aims to determine the description of substance P in children with atopic dermatitis using a descriptive observational study with a cross-sectional approach. Methods: This is a destructive observational study with a crossectional approach samples were selected from AD patients at the Universitas Sumatera Utara Hospital. Result: The largest group of subjects were childhood (2–12 years old), there was 60%, followed by the adolescent group (12–18 years old) and the infant group (<2 years old). In the childhood group, the highest level of substance P was found in girls with a mean of 349.03 ± 146.7. On the other hand, the highest levels of substance P in the adolescent were found in males with a mean of 243.73 ± 64.57 ng/L. Conclusion: In this study, we found that the level of substance p was higher in the childhood group.